2021
DOI: 10.3390/agronomy11071345
|View full text |Cite
|
Sign up to set email alerts
|

Bambara Groundnut (Vigna subterranea [L.] Verdc.) Production, Utilisation and Genetic Improvement in Sub-Saharan Africa

Abstract: Bambara groundnut (Vigna subterranea [L.] Verdc.) is a nutritionally rich grain legume crop indigenous to Africa. It is tolerant to drought stress and has become adapted to grow under low input and marginal agricultural production systems in Africa and Asia. Bambara groundnut is an orphan crop, and represents a neglected and under researched plant genetic resource. Modern crop management, production technologies, and value chains are yet to be developed in Africa to achieve the potential economic gains from Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
57
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(61 citation statements)
references
References 69 publications
3
57
1
Order By: Relevance
“…Hence, the highest production of the crop should be from the southern part of the continent. This view is confirmed by Majola et al (2021) , who reported the southern African region as the suitable region in the continent for the production of BGN. Despite its reported qualities, one of the critical challenges facing BGN production and other underutilized legumes is their low yield when compared to the major crops ( Sidibé et al, 2020 ; Temegne et al, 2020 ).…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…Hence, the highest production of the crop should be from the southern part of the continent. This view is confirmed by Majola et al (2021) , who reported the southern African region as the suitable region in the continent for the production of BGN. Despite its reported qualities, one of the critical challenges facing BGN production and other underutilized legumes is their low yield when compared to the major crops ( Sidibé et al, 2020 ; Temegne et al, 2020 ).…”
Section: Introductionsupporting
confidence: 59%
“…Using this techniques thus enable higher yields and avoid crop failure ( Muthamilarasan et al, 2019 ). Insect pests that have been observed to be attacking BGN have been reported ( Lale and Vidal, 2003 ; Majola et al, 2021 ). An understanding of these pests’ biology, including their mode of action, and the various host defenses that organisms use to resist insect pests is critical for the development of insect-tolerant varieties.…”
Section: Mainstreaming Bambara Groundnut For Ensuring Food and Nutritional Securitymentioning
confidence: 99%
See 1 more Smart Citation
“…This legume seed crop was reported to originate from West Africa from the Bambara district near Timbuktu ( Jideani and Diedericks, 2014 ) but is now widely grown in Africa, Malaysia, South, and Central America, some parts of Northern Australia, Sri Lanka, and Indonesia ( Azam-Ali et al, 2001 ). Different places have their indigenous names for BGN for example in Malawi (Madagascar groundnut, Baffin pea, Voandzou, Indhlubu, underground bean, Nzama), Nigeria (Epa-Roro), South Africa (Jugo beans), and Zimbabwe (Nyimo beans; Emelike and Barber, 2018 ; Majola et al, 2021 ; Olanrewaju et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, BGN reportedly ticks the box for achieving food security crop ( Massawe et al, 2016 ; Halimi et al, 2019 ; Olanrewaju et al, 2022 ). It is available, accessible, and affordable, and it is a source of income for farmers in sub-Sahara Africa due to its ability to tolerate drought and fix atmospheric nitrogen ( Paliwal et al, 2020 ; Majola et al, 2021 ; Olanrewaju et al, 2021c ). Furthermore, it cross-nodulates with nitrogen-fixing bacteria from other leguminous plants like cowpea ( Laurette et al, 2015 ; Hassen et al, 2022 ) which further enhances its nitrogen-fixing ability.…”
Section: Introductionmentioning
confidence: 99%